Comparison of metastatic versus non-metastatic breast cancer at the time of diagnosis and risk factors for primary metastatic breast cancer (Annals of Medical Research, 2023)
Aim: The most common type of cancer in women is breast cancer. Despite an increase in the rate of early detection, distant organ metastasis is still seen at the time of diagnosis. The purpose of this study was to identify the predictive risk factors for breast cancer patients with distant organ metastases and to compare them to those without distant organ metastases.Materials and Methods: The study included data from patients who applied to our clinic for follow-up or treatment between January 2020 and July 2020. After meeting the exclusion criteria, the remaining 115 patients were included in the study. Study participants were divided into two groups: metastatic (group I) and non-metastatic (group II). Logistic regression analysis is used to assess the predictive risk factors.Results: There is a significant difference between groups in terms of the breast side, T-stage, N-stage, CA 15-3, and albumin levels (p< 0.05). In univariate analyses, T-stage, CA 15-3, estimates glomerular filtration rate (eGFR), alkaline phosphatase, and albumin levels were statistically found to be significant (p
Keywords: Breast cancer; Metastasis; CA 15-3; Albumin